Antioxidant and anti-foodborne bacteria activities of shiitake by-product extract in fermented sausages. (December 2016) - Van Ba, Hoa; Seo, Hyun-Woo; Cho, Soo-Hyun; Kim, Yoon-Seok; Kim, Jin-Hyoung; Ham, Jun-Sang; Park, Beom Young; Pil Nam, Seong
Abstract: The effect of addition of extract from shiitake by-products (0, 0.3, and 0.6%) on the quality characteristics, lipid oxidation and microbial stabilities of fermented sausages was studied during storage up to 30 days at 15 °C, and its effect was also compared with those produced with synthetic antioxidant, BHT (0.02%) or nitrite (0.01%). The addition of natural extract resulted in lower ultimate pH values with higher number of lactic acid bacteria, lower lipid oxidation level and spoilage bacteria count in the products during storage as compared with those of the control or BHT and nitrite treatments ( P  < 0.05). Storage time significantly increased the lipid oxidation level, however, the increasing rate after 30 days storage in the following order: Control (increased by 1.22 mg MDA/kg) > 0.02% BHT (increased by 0.43 mg MDA/kg) > 0.01% nitrite/nitrate (increased by 0.42 mg MDA/kg) > 0.3% SSE (increased by 0.34 mg MDA/kg) > 0.6% SSE (increased by 0.18 mg MDA/kg). Furthermore, extract of fermented sausages fortified with 0.6% shiitake stipes extract also showed strong antimicrobial activity against 3 foodborne bacteria such as Staphylococcus aureus (minimum inhibitory concentrations (MIC) = 2.08 mg/mL), Listeria monocytogenes (MIC = 4.16 mg/mL) and Escherichia coli O157 (MIC = 8.33 mg/mL). Additionally, the addition of the extract did not cause defects of color, texture and sensory quality in the products. Our results clearly suggest that the shiitake by-product extract represents a functional ingredient to be used (at level of 0.6%) for improving lipid oxidation and microbial stabilities as well as controlling the growth of pathogens in fermented sausages. Highlights: Fermented sausages were fortified with 0.3 and 0.6% shiitake stipe extract (SSE). The addition of SSE resulted in lower pH and higher lactic acid bacteria count. The use of SSE inhibited lipid oxidation and spoiled bacteria growth during storage. The fermented sausages extract had antimicrobial activity against 3 pathogens. The use of SSE did not cause color, texture and sensory defects in the product.